Pole vault landings and injury - Boden, B. P.; Johnson, J. (Track Coach, 2017)
The purpose of this study was to investigate and report the serious and catastrophic injuries to pole vaulters 2003-2011 and to compare it to our long-term data base of known serious and catastrophic injuries, dating to 1971. And to investigate the potential protective capabilities of materials for padding the hard surfaces around pole vault landing systems. Attention was focused on the padding in and around the plant box since it was reported to be the location of 74% of the catastrophic accidents during the 2003 to 2011 time span (3), and over 50% of the 1971-2016 data. Additionally, the plant box area offered the greatest challenge since several mechanical criteria must be met which limit the amount of padding in this critical area.